MEDIA DISCOURSE: MEDIA TRANSLATION AND NECESSITY OF STUDYING IT - Diyorova Mahliyo (Лучшие интеллектуальные исследования, 2023)
Amidst the swift advancements in technology, diverse communication modalities, and the growing significance of information in societal affairs, informational genres across various media platforms assume particular significance. They currently face fierce competition from alternative information creation and reception methods made possible by new technologies. The advancement of human society is dependent on verbal communication. The majority of the information that the media provides today interests us all. It is hard to picture our lives without information from the mass media. The people of Kazakhstan can access a variety of television news programs in multiple languages thanks to the advancements in modern communication technology. Furthermore, in accordance with the trinity of languages cultural projectModern society seeks to orient itself to the sociopolitical life of a republic and a common world.